Linguistische Gutachten für Patente - Nickl, Markus (HERMES - Journal of Language and Communication in Business, 2006)
A patent is a special kind of text which has to comply with legal requirements, which is categorized by its strictly binding character, by its high ﬁnancial potential and by its long-lasting validity. That is reason enough to take a closer look at the linguistic aspects of patents. Therefore doctima GmbH has developed a special offer for its clients to analyse patents as regards linguistic weak points. First, this article deals with the economic and operational aspects of patents. Second, characteristic features of the text of patents are analysed. Finally, doctima’s speciﬁc range of products concerning reports on patents is presented and its beneﬁt for companies and patent agents is demonstrated.